Peran Ziswaf dalam Memulihkan Ekonomi Umat Akibat Masa Pandemi Covid-19 - Amirudin, Choirul (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
This research was conducted with the aim of providing solutions and the role of one the Islamic economic instruments, namely zakat, infaq, alms and waqf which can be applied in dealing with economic problems due to the Covid-19 pandemic. In conducting research, researchers used a library research approach and content analysis techniques. The results of the research that show that Ziswaf can be a solution and role to restore the economy due to the Covid-19 pandemic are as follows: (1) Make each village an UPZ to maximize zakat (2) maximize cash zakat and productive zakat (3) maximize zakat and infaq management (4) providing educational assistance for students affected by Covid-19, which is prioritized forstudents majoring in sharia economics so that in the future they can educate the public about Islamic economics.